Role of Mitral Annular Systolic Velocity in The Evaluation of Left Atrial Appendage Function in Mitral Stenosis - Majumder, AAS; Tanveer, MS; Reza, AQM; Chowdhury, AW; Shahabuddin, M (Cardiovascular Journal, 2011)
Background : Mitral stenosis (MS) is the most common valvular heart disease. Thromboembolism is one of the most important complications of MS, especially when it is associated with atrial fibrillation (AF).Patients with sinus rhythm (SR) are also sussceptible to this complication when it is associated with left atrial appendage (LAA) dysfunction .LAA dysfunction is an independent predictor of thromboembolism in mitral stenosis. Objectives: To investigate whether there is a relation between mitral annular velocities obtained by Doppler tissue imaging (DTI) and LAA function determined by transoesophageal echocardiography (TEE) and to determine if the annular velocities can predict the presence of the inactive LAA in MS. Methods: Sixty MS patients were evaluated by transthoracic echocardiography and all patients underwent transesophageal echocardiography. The annular systolic (S-wave) and diastolic (Emand Am-waves) velocities were recorded. Inactive LAA was defined as LAA emptying velocity <25 cm/sec. Patients were divided into three groups; group AI (n = 18): sinus rhythm (SR) and LAA emptying velocity e”25 cm/sec, group AII (n =22): SR and LAA emptying velocity <25cm/sec and group B (n = 20): atrial fibrillation. Results: Thrombus was detected in 14 patients and spontaneous echo contrast (SEC) was detected in 48 patients. Both S-wave and peak LAA emptying velocities were decreasing, while SEC frequency and density were increasing from group A to group B. There was a positive correlation between LAA emptying vs. S-wave and LAA emptying vs. Am velocities (p < 0.001, r = 0.708 and p< 0.001, r=0.495). Multivariate regression analysis showed that only S-wave is the independent predictor of inactive LAA (p = 0.001, odds ratio = 0.133, 95% CI = 0.032–0.556). In patients with SR, the cutoff value of S-wave was 14 cm/sec for the prediction of the presence of inactive LAA (sensitivity: 92.3%, specificity: 95.3%). Conclusions: S-wave is an independent predictor of inactive LAA and a useful parameter in estimating inactive LAA in MS with SR.. Key words: Mitral stenosis, Left atrial appendage function, Annular systolic velocity DOI: http://dx.doi.org/10.3329/cardio.v1i1.8201 Cardiovasc. j. 2008; 1(1) : 26-33